2021
DOI: 10.7150/thno.59293
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and severe coronavirus disease 2019: molecular mechanisms, paths forward, and therapeutic opportunities

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) appears to have higher pathogenicity among patients with obesity. Obesity, termed as body mass index greater than 30 kg/m 2 , has now been demonstrated to be important comorbidity for disease severity during coronavirus disease 2019 (COVID-19) pandemic and associated with adverse events. Unraveling mechanisms behind this phenomenon can assist scientists, clinicians, and policymakers in responding appropriately to the COVID-19 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 186 publications
0
23
0
1
Order By: Relevance
“…Apparently, humoral immunity is not affected, and people with diabetes mellitus have deficits in neutrophil function and alterations in the phenomena of chemotaxis, adhesion, and phagocytosis and also in the intracellular destruction of pathogenic microorganisms [ 55 ]. Patients with T2DM usually have an excess of adipose tissue, which, according to pathophysiological processes, can trigger an alteration of glycemic homeostasis, produce some important alterations such as chronic inflammatory state and chronic hyperglycemia, which cause a negative effect on patients with respect to immunity and make them more susceptible to infections—in this case, to the infection caused by SARS-CoV-2 [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apparently, humoral immunity is not affected, and people with diabetes mellitus have deficits in neutrophil function and alterations in the phenomena of chemotaxis, adhesion, and phagocytosis and also in the intracellular destruction of pathogenic microorganisms [ 55 ]. Patients with T2DM usually have an excess of adipose tissue, which, according to pathophysiological processes, can trigger an alteration of glycemic homeostasis, produce some important alterations such as chronic inflammatory state and chronic hyperglycemia, which cause a negative effect on patients with respect to immunity and make them more susceptible to infections—in this case, to the infection caused by SARS-CoV-2 [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanisms associated with SARS-CoV-2 infection involves an increase in inflammation, leading to an increase in cytokines (cytokine storm) in patients with COVID-19 [ 30 ], mainly manifested by an increase in interleukin IL-2, IL-7, INFÎł, and TNFα, leading to suppression of NF-kB activity, resulting in decreased expression of COX-2 [ 31 ]. Among all interleukins, IL-6 was found to be associated with highly pathogenic SARS-CoV-2 infection, due to enhanced virus replication mainly in the lower respiratory tract [ 32 , 57 ] ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other laboratory blood tests such as C-reactive protein (CRP) level, D-dimer, complete blood count (CBC) is also done to know about inflammatory and coagulation level of the individuals. It has been observed that patients with comorbid conditions like diabetes, obesity, hypertension, etc are more likely to get into serious conditions ( Rahman et al, 2021 ; Yan et al, 2021 ). Many researchers across the globe are working on the development of new chemical entities (NCEs) against this infection, however, no specific drugs are available in the market for its treatment so far ( Singhal, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) reports that since 1975, the number of obese people in the world has grown nearly three-fold, and currently, nearly 20 million adults are overweight or obese [1]. Obesity not only affects one's physical appearance but also causes various diseases [2] that burden the economy and the medical and health infrastructure. At present, popular methods of weight loss include dieting, targeted drug therapy, and surgical liposuction.…”
Section: Introductionmentioning
confidence: 99%